The The Effect of Job Crafting on Employee Well-Being in Brachial Plexus Injury (BPI) Patients - Sri Wahyuni, Endang; Febri Arifiati, Retna (Poltekkes Kemenkes Surakarta, 2024)
Background: Brachial Plexus Injury (BPI) is a peripheral nerve injury that can cause functional disorders of the upper limbs due to decreased range of motion of joints and muscle strength. Further impacts can include psychological stress, socioeconomic difficulties, reduced quality of life, and ability to work. Patients who are unable to return to work require job crafting to create a balance between job demands and job resources so that they can achieve employee well-being. The general objective of this study is to determine the effect of job crafting on the level of employee well-being in BPI patients. The benefits of the results of this study will later be used to improve outcome measurement and recommendations in determining therapy goals, especially in the area of productivity, so that independent, productive, and prosperous BPI can be realized. Methods: This research is quantitative research with a pre-experimental research form. The type of approach used is comparative, using a group pre- and post-test design. The research was conducted in the BPI community of East Java using purposive sampling techniques, and 30 research subjects were obtained. Results: The results of the study showed that the majority of research subjects were in the age range of 19-44 years (adults) as much as (80%), male gender (76.7%), and dominated by workers in the private sector (96.7%). The results of the hypothesis test using the paired sample t-test obtained an ρ value of 0.001. Conclusion: job crafting has an effect on employee well-being in BPI patients.